Levels of Speaking Anxiety Among English Education Students in Classroom Presentation Activities - Nova Herlianah; Intan Permata Hapsari (Universitas Islam Negeri Palopo, 2026)
Speaking anxiety is a common problem for students who learn English as a Foreign Language (EFL), especially when they have to give presentations in class. This study aims to find out the level of speaking anxiety among English Language Education students during classroom presentations and to identify the factors that cause their anxiety. This study used a descriptive quantitative method. The participants were 34 English Language Education students from the fourth, sixth, and eighth semesters at a state university in Indonesia. The data were collected through a questionnaire consisting of 30 statements based on Foreign Language Anxiety Theory, Communication Anxiety, and the Affective Filter Hypothesis. The data were analyzed using IBM SPSS Statistics version 25 through validity and reliability tests, as well as descriptive statistical analysis. The results showed that all questionnaire items were valid and highly reliable. The findings also showed that most students experienced a moderate level of speaking anxiety during classroom presentations. The main causes of anxiety were fear of making grammar mistakes, forgetting vocabulary while presenting, fear of being judged by others, and feeling embarrassed when making mistakes in front of classmates. These findings show that speaking anxiety is still a major challenge for English Language Education students and may affect their confidence and presentation performance. Therefore, teachers should create a supportive classroom atmosphere and provide more opportunities for presentation practice to help students reduce anxiety and improve their speaking skills.